The ERF11 Transcription Factor Promotes Internode Elongation by Activating Gibberellin Biosynthesis and Signaling. Issue 4 (2nd June 2016) - Zhou, Xin; Zhang, Zhong-Lin; Park, Jeongmoo; Tyler, Ludmila; Yusuke, Jikumaru; Qiu, Kai; Nam, Edward A.; Lumba, Shelley; Desveaux, Darrell; McCourt, Peter; Kamiya, Yuji; Sun, Tai-ping
Abstract : The transcription factor AtERF11 promotes stem growth by increasing GA biosynthesis and GA response in Arabidopsis. Abstract: The phytohormone gibberellin (GA ) plays a key role in promoting stem elongation in plants. Previous studies show that GA activates its signaling pathway by inducing rapid degradation of DELLA proteins, GA signaling repressors. Using an activation-tagging screen in a reduced-GA mutant ga1-6 background, we identified AtERF11 to be a novel positive regulator of both GA biosynthesis and GA signaling for internode elongation. Overexpression of AtERF11 partially rescued the dwarf phenotype of ga1-6 . AtERF11 is a member of the ERF (ETHYLENE RESPONSE FACTOR) subfamily VIII-B-1a of ERF/AP2 transcription factors in Arabidopsis ( Arabidopsis thaliana ). Overexpression of AtERF11 resulted in elevated bioactive GA levels by up-regulating expression of GA3ox1 and GA20ox genes. Hypocotyl elongation assays further showed that overexpression of AtERF11 conferred elevated GA response, whereas loss-of-function erf11 and erf11 erf4 mutants displayed reduced GA response. In addition, yeast two-hybrid, coimmunoprecipitation, and transient expression assays showed that AtERF11 enhances GA signaling by antagonizing the function of DELLA proteins via direct protein-protein interaction. Interestingly, AtERF11 overexpression also caused a reduction in the levels of another phytohormone ethylene in the growing stem, consistent with recent finding showing that AtERF11 represses transcription of ethylene biosynthesis ACS genes. The effect of AtERF11 on promoting GA biosynthesis gene expression is likely via its repressive function on ethylene biosynthesis. These results suggest that AtERF11 plays a dual role in promoting internode elongation by inhibiting ethylene biosynthesis and activating GA biosynthesis and signaling pathways.